Using a music microanalysis protocol to enhance instrumental practice - López-Íñiguez, Guadalupe; McPherson, Gary E. (Frontiers in Psychology, 2024)
The strategies that enable musicians to adapt their behaviors so that they can break through, feel energized, and perform well collectively distinguish what it is to be a self-regulated learner. These strategies range from one’s ability to monitor thoughts and actions to being able to navigate and control one’s emotions, especially when feeling frustrated or anxious. Given the challenges of the music profession, it becomes imperative for teachers to equip their students with the necessary skills to self-regulate their own actions, feelings, and thinking so that they are eventually able to cope with the demands required of a contemporary professional musical career. In this study, we focused on the self-regulatory engagement of four master’s level cellists who were enrolled in a prominent European higher music education institution. Our data comprised self-regulated learning-based diary-reports that describes the students’ practice of self-chosen, especially demanding passages as they prepared for a public recital. Results depict differences between the musicians according to the efficiency of their practice leading up to a formal public recital.